The moderating effects of degree of internationalization on factors affecting the international performance of small and medium enterprises in the Malaysian Halal Food Industry. - Ismail, Noor Azlin (2011)
This study examines the influence of small and medium enterprises’ (SMEs’) specific internal capabilities, external environment and degree of internationalization based on speed, scale and scope on their internationalization process and performance. It looks specifically at the performance of the SME halal food exporters from/in Malaysia holistically. This is significant because earlier studies have largely ignored performance of firms operating in different cultural and religious settings. Furthermore, the context within which the firm acts has changed considerably particularly due to the globalization phenomenon. As such, SMEs’ have had to understand the interplay between the various internal and external factors and the strategic choice of the internationalisation process and how these will affect their performance. Therefore, theories need to evolve to account for these new behaviours. This study uses existing theories based on Stage Theory-Uppsala Model, Resource Based View (RBV), International New Venture (INV), Dynamic Capability View, Contingency View, Industry-Based View and Institutional Based View, incorporating various internal and external factors that are related to international business and international entrepreneurship fields of study. In terms of methodology, this is a quantitative study. Three hundred (300) structured questionnaires were mailed to the SME exporters in Malaysia and 174 completed questionnaires were returned from 195 respondents. To answer the research objectives, Descriptive analysis, Multiple Linear Regressions (MLR) and Moderated Multiple Regression (MMR) analyses were executed to determine the significance of the relationships between SMEs’ specific internal capabilities, external environment factors and moderating effects on their international performance. Based on the six hypotheses proposed, and using MLR analysis, the results indicate that there are significant relationships between some of SMEs’ specific internal capabilities (foreign experiential knowledge and halal reputation), external environment (globalization phenomenon, industry and domestic market, institutional factors) and international performance. The findings confirm that SMEs’ international performance is influenced by the interplay between some of their internal capabilities and external environment factors. In addition, based on the impact of three moderator variables analysed by MMR to differentiate between traditional incremental versus rapid internationalization process, the findings reveal that speed and scale are not supported. However, scope level has significant positive impact on some of SMEs’ specific internal capabilities (foreign experiential knowledge, founder/managers international experience, global mindset, international entrepreneurial orientation and halal reputation) and international performance. The scope level is categorized into regional firms operating in low scope and global firms operating in high scope. As a result, there exist differences in terms of their internal resources (competitive advantage), and international performance where firms that are global show better position than regional. In conclusion, these findings would enable academicians, practitioners and government agencies to focus on the pertinent and related issues of differences between these two types of SME exporters in terms of their internal resources, external environment, market scope (regional versus global) and international performance from a holistic point of view, religious products and country origin perspectives.